Pengaruh Kepuasan Kerja dan Stres Kerja terhadap Turnover Intention pada PT Bank OCBC NISP Tbk Area Jakarta Pusat - Arief Rachman Hakim; Raden Joko Sugiharjo (Universitas Mercu Buana, 2018)
ABSTRACT This study to determine the effect of Job Satisfaction and Job Stress on Turnover Intention. The object of this research is PT Bank OCBC NISP Tbk Central Jakarta Area. This research is a causal associative research using quantitative approach done to 86 respondents. This study explains the influence and influence of the variables to be studied, using multiple linear regression analysis method. From the results of this study showed that the variable of Job Satisfaction Not Significant To Turnover Intention. While the variable of Work Stress has significant effect to Turnover Intention. Keywords : Organizational Culture, Training Program, Compensation, Employee Loyalty